Extraction and visualization of orientation data from virtual geologic surfaces with MATLAB® - Avery J. Welker; John P. Hogan; Andreas Eckert (MethodsX, 2019)
High-resolution visualization of surfaces of geologic interest, at a multitude of scales, using 3D point cloud technologies provides an opportunity to analyze spatial relationships of surfaces using orientation data. We present a MATLAB® script that produces planar geologic attitude data (e.g., strike, dip, and dip-direction data) from 3D datasets (e.g., point clouds, 3D scanning). The method utilizes Cartesian coordinates of triangular planar surfaces and converts them into matrices of conventional geologic attitude data. Spatial relationships among data points can be investigated, using polar tangent diagrams, stereographic analysis, or geologic curvature analysis. We utilize this script to create “synthetic” graphical plots (e.g., stereograms, tangent diagrams) from geomechanically realistic, virtual, folded surfaces produced by dynamic modeling. Synthetic graphical diagrams are of considerable usefulness in interpreting graphical plots (e.g., stereograms) of attitude data from natural folded rock surfaces, particularly in locations with poor exposure. • This script outputs attitude data (strike, dip, and dip direction) in a spreadsheet and as a text file for use in other visualization software. • A tangent diagram is created and displayed in this script for rapid visualization and fold shape assessment. • The MATLAB script is readily modified to accept multiple data formats for input (e.g., MATLAB variables, *.csv files, etc.) and output (e.g., *.csv files, *.txt files, etc.). Method name: Using MATLAB® to extract and visualize planar geologic attitudes from point-based data, Keywords: Planar data visualization, Structural geology, Stereographical analysis, Polar tangent diagram